Supervisors' role quality and its effect on the students' ability in compiling reports - Husnaeni, Husnaeni; Burga, Muhammad Alqadri (LPMPP Universitas Negeri Yogyakarta, 2024)
The reality of the lack of students understanding regarding the PTK principles so that they plagiarism and have difficulties compiling reports are the supervisors' unresolved responsibility. This research was aimed at analyzing the role quality on first and second supervisors at performing their tasks as supervisors for the subject PKP and their influences on students' abilities in writing the PKP reports. This is a survey research using a correlational quantitative approach. About 143 respondents were selected purposively consisting of 15% at all 953 population (total students of following the subject PKP at PGSD UPBJJ-UT Makassar). The data collecting method utilized questionnaires, documentation, and observation. Data were analyzed utilizing descriptive and differential statistic techniques. Results of this research indicate that (1) the role quality of both supervisors is in the highest category, while the students' capability in writing the PKP reports is at a high level. (2) The role quality of these supervisors both partial and simultaneous conditions, is affected positively and significantly on writing the PKP reports. Based on calculating the determinant coefficient, the role quality of these supervisors delivers a relatively small influence namely about 9.1% for writing PKP reports of students.